Análisis e interpretación a los estados financieros a la fundación privada Fepp (Fondo ecuatoriano populorum progressio), del cantón Lago Agrio, período 2013-2014 - Sanchima Loyaga, Amelia Eufemia (2017)
In the realization of the present work of research, is justifies because is necessary put in practice all them knowledge acquired during the period academic in them classrooms of the University national of Loja, in where the process of research linked with the community, has contributed to generate this work and provide with a society more fair and solidarity also will allow meet with one of them requirements established in the regulation of regime academic , prior to obtaining the title of engineer in accounting and audit CPA. For meet with the approach of them objectives proposed in the development of the present work of thesis is made the application of the analysis financial Horizontal, Vertical and application of indicators financial, with the purpose of determine them possible risks and also of know the level of indebtedness on which is manages it Foundation, with the purpose of offer a tool required of agreement. Additionally is leaves them recommendations for provide in them decisions management, so also is socializes on the importance of follow with the practice of the analysis financial at least one time to the year, as well as the application of them indicators financial, for based on them results quantitative and qualitative take decisions and/or corrective.